2018
DOI: 10.1111/eip.12697
|View full text |Cite
|
Sign up to set email alerts
|

Medication, hospitalizations and mortality in 5 years after first‐episode psychosis in a Swedish nation‐wide cohort

Abstract: The proportion of cases dispensing antipsychotics decreases year by year after first discharge. Mortality and rates of rehospitalization also decrease year by year from high levels the first year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…PANSS was used worldwide to estimate psychiatric symptoms for decades. Versions of the five-factor model have been used in diverse SCZ research areas including positive symptom, negative symptom, cognitive defect, hostility/excitement symptom and anxiety/depression symptom ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PANSS was used worldwide to estimate psychiatric symptoms for decades. Versions of the five-factor model have been used in diverse SCZ research areas including positive symptom, negative symptom, cognitive defect, hostility/excitement symptom and anxiety/depression symptom ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…The existing studies have tried to identified several factors predicting the risk of suicide in individuals with SCZ, which include younger age, male gender, lack of social support, unemployment, being unmarried, being well-educated, being intelligent ( 21 ), a family history of psychiatric disorder, having poor work functioning, higher number of hospitalizations ( 25 ), presence of a previous suicide attempt, poor adherence to treatment, history of suicidal behavior ( 20 ), having had recent (i.e., within past 3 months) life events ( 26 ), having access to lethal means, and seriousness of psychiatric pathology ( 21 ), comorbid affective disorder and the strong stigma of mental illness in rural areas ( 16 ). Furthermore, some studies have also reported that a combination of genetic markers and early traumatic life events might indeed be used to identify patients at risk for suicide attempt in SCZ.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with pre-onset self-harm had overall higher levels of positive symptoms during follow-up than did individuals without pre-onset self-harm. Most previous research has aggregated self-harm with suicide attempts, and pre-onset with post-onset phases, and found mixed evidence of associations with positive or negative symptoms (Ayesa-Arriola et al, 2015; Challis et al, 2013; Strålin & Hetta, 2019; Togay et al, 2015). To our knowledge, no previous study has specifically examined pre-onset self-harm.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a large number of patients demonstrate only partial response to antipsychotic treatment 5 , and a substantial minority of first episode patients demonstrate robust response (defined either as 50% reduction in positive symptoms 4 or as absence of frank psychosis 6,7 ). The first episode of illness is especially important clinically for at least three reasons: 1) it is the phase of illness associated with the greatest risk of suicide 8,9 ; 2) it may be the best opportunity to mitigate long-term illness trajectory 10 ; and 3) the onset period of late adolescence/early adulthood represents a critical period for attaining functional milestones in the transition to independence 11 . Thus, identification of individuals at risk for poor response is an important clinical goal, yet prognostic biomarkers are lacking 12 .…”
Section: Tablementioning
confidence: 99%